The Effect of Foreign Sell, Required Return, Expected Return, Actual Return, and Risk on Herding Behavior - Pristin Prima Sari; Ardian Prima Putra; Harmadi Harmadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study is motivated by the phenomenon of herding behavior in the capital market, which is influenced by various financial factors, including foreign sell, required return, expected return, actual return, and risk, particularly in manufacturing companies listed on the Indonesia Stock Exchange during the 2024–2025 period. The objective of this study is to obtain empirical evidence regarding the effect of these variables on herding behavior in January and December 2024–2025. The method employed is a quantitative approach through hypothesis testing using data from manufacturing firms as the research sample. The results indicate that in January, actual return and beta risk have a significant effect on herding, and simultaneously, all variables significantly influence herding behavior. Meanwhile, in December, required return and expected return are found to have a significant effect on herding. The difference test reveals significant differences in expected return and actual return between January and December. The implications of this study provide insights for investors and companies in understanding market behavior and formulating more rational investment strategies. In conclusion, return and risk factors play a crucial role in shaping herding behavior in the Indonesian capital market.